Development of a mindful parenting model for mothers with children in early childhood - Hidayati, Fina; Hartini, Nurul; Chusairi, Achmad (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Mothers’ care of young children determines their well-being physically, emotionally and cognitively. It is important to practice effective parenting with affection, unconditional acceptance and care, an approach known as mindful parenting. This study aims to develop a mindful parenting model based on perceived social support, self-compassion, confidence in parenting, and gratitude as mediator variables in mothers of young children. A quantitative approach is taken, with purposive sampling employed. The study respondents were 303 mothers with children in early childhood (3-6 years), aged 20-36, living at home with their children, and residing in cities/districts in East Java province, Indonesia. The instruments used to measure mindful parenting were the Mindfulness in Parenting Questionnaire (MIPQ), Self-compassion with Skala Welas Diri (SWD), Parental Self-efficacy with Self-Efficacy Parental Task Index (SEPTI); and Perceived Social Support with Interpersonal Survey Evaluation List (ISEL) Analysis was conducted using the path analysis technique. The study results indicate that a mindful parenting model can be built based on the perceived social support of mothers, self-compassion, and mothers’ perceptions of self-efficacy in parenting, which are fully mediated by the gratitude of mothers for their young children, with a value of Q² = .274 or 27.4%. This finding suggests that gratitude is a major factor that enables mothers to practice mindful parenting. The research findings can be used to help develop intervention programs for parents, specifically mothers of young children, and related stakeholders, and can also be developed in future research.